2021
DOI: 10.1039/d1cc01673c
|View full text |Cite
|
Sign up to set email alerts
|

A novel theranostic activity-based probe targeting kallikrein 7 for the diagnosis and treatment of skin diseases

Abstract: We applied a new in silico approach for fishing protease-substrate motifs to design a kallirein 7 (KLK7)-specific phosphonate activity-based probe (ABP) to quantify the active KLK7 in situ. Epidermal application...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 17 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…Regarding the carbon stereocenter, we have previously showed that the R state is prevalent. 18 In respect to the P atom stereochemistry, the R diastereomer of compound 13 showed much higher binding scores towards both chymotrypsin A (Fig. 6A) and KLK7 (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Regarding the carbon stereocenter, we have previously showed that the R state is prevalent. 18 In respect to the P atom stereochemistry, the R diastereomer of compound 13 showed much higher binding scores towards both chymotrypsin A (Fig. 6A) and KLK7 (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Overall, these dockings are consistent in terms of general docking orientation in respect to similar compounds described in our previous work. 18 The Cy5 group interacts with the same region of KLK7 as well as chymotrypsin A, namely S1′. Notable differences are the benzyl – F218 and tert -butyl – W215 and L175 interactions with KLK7 (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations